COST ESTIMATE FOR THE MONTHLY SET UP AND OPERATION OF A TELECONSULTATION ROOM - Delphino, Tallita Mello; Santana, Rosimere Ferreira; Rodrigues, Julianna Nogueira; Cassiano, Keila Mara (Cogitare Enfermagem, 2023)
Objective: to estimate the cost of setting up and monthly operation of a teleconsultation room. Method: descriptive study, carried out by means of a survey of direct and indirect costs for setting up and monthly operation of a teleconsultation room in Niterói - RJ - BR. The data analysis was based on discrimination of the type and quantity of equipment needed to set up the room; and on budgets obtained through research in public tenders and commercial stores. To estimate the running costs, the following were considered: monthly electric power consumption; costs with telephone network, materials, and supplies; and with nurses. Results: the minimum cost to set up the room was R14,904.17 reais. The average monthly cost for 30 hours per week with three nurses was R14,706.95. Conclusion: it is believed that teleconsultation can improve access to health care, quality of care and reduce costs related to the health system.